“Quão atemorizante é este lugar! Não é senão a casa de deus e este é o portão dos céus”: prolegômenos à hermenêutica do discurso religioso e do comportamento das testemunhas de Jeová na associação torre de vigia de bíblias e tratados - Dias, Cleberson (2016)
The main purpose of this research was to analyze, focusing on the hermeneutic perspective, the relationship between religious speech, originated from the biblical exegesis made by the Governing Body of Jehovah's Witnesses, and the standardization and organization of behavior, in particular, of the witness of Jehovah serving at Bethel, community fundamentally interconnected with the Association Watchtower Bible and Tract, which is basically their legal reason, located on Highway SP-141, Km 43, in Cesario Lange / SP. This is the place where all the preaching work is organized and publications are translated, printed and distributed for free during the preaching process. As a central character, the bethelite provided all the necessary content to our research. His daily experience was widely considered in the analisys from the subject behavior inside the total instituitions, within the same proportion in which we assessed theorical basis of understanding the faith experience and its deployment Michel Foucault and Erving Goffman offered support hermeneutic for understanding the religious discourse in Bethelite behavior. This was the analysis and understanding of religious experience in everyday life level, in their practices and contradictions, within the context of the headquarters of Jehovah‘s Witnesses in Brazil. The project aimed to answer the following problem: what is observed in Bethel can be described as alienation and domestication of behavior or as a conscious and sincere desire for inner discipline and collaboration in the production of all materials used in the ―preaching‖ of Jehovah's Witnesses? Beforehand, this dichotomy has justified the need to put the ―Tower under watching.‖